1986
DOI: 10.1177/07399863860084004
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Bilingual Education on Secondary School Grades, Attendance, Retentions and Drop-Out

Abstract: Junior high and high school academic performance of two groups of students were compared in a quasi-experimental study. The experimental group students (N = 86) had received one or more years of bilingual instruction at the elementary level while the control group students (N = 90) had not participated in an elementary bilingual program. While differences in grade-point average (GPA) and absenteeism were small, the bilinguals were less likely to drop-out and experienced fewer retentions. Secondary analyses foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The majority of work analyzing ELA programs involves elementary school students, although a few exceptions exist. For example, Curiel, Rosenthal and Richek (1986) find some evidence in favor of BE at the junior high and high school levels. Conversely, Ho (1985) fails to uncover empirical advantages for native-language instruction versus English-immersion in six academic subjects but one (economics/public affairs) for eighth graders.…”
Section: Supporting Evidence In Favor and Against Ela Programsmentioning
confidence: 99%
“…The majority of work analyzing ELA programs involves elementary school students, although a few exceptions exist. For example, Curiel, Rosenthal and Richek (1986) find some evidence in favor of BE at the junior high and high school levels. Conversely, Ho (1985) fails to uncover empirical advantages for native-language instruction versus English-immersion in six academic subjects but one (economics/public affairs) for eighth graders.…”
Section: Supporting Evidence In Favor and Against Ela Programsmentioning
confidence: 99%
“…Academic instruction.If cognitive factors are considered, children with higher IQs are less likely to drop out of school than are those with lower assessed intelligence, although familial factors (e.g., maternal depression) may outweigh any protective influence of high cognitive ability (Bohon et al, 2007). Several intervention studies used intensive academic instruction in the basic skills of mathematics, reading, and language arts for children identified as at risk for school failure (Curiel, Rosenthal, & Richek, 1986;Meyer, 1984;Temple et al, 2000). Based on information in the available literature, it appears that most supports for teachers (e.g., teacher aides, classroom volunteers) that allow for time for basic skills instruction are most prominent in the elementary grade levels (K-6), with relatively little support of this kind available in the higher grades.…”
Section: Strategies Addressing Risk Factorsmentioning
confidence: 99%
“…Cummins's second hypothesis, a dual-level threshold hypothesis, supports the initial development of bilingual learners' L 1 proficiency to avoid early negative effects on their cognitive growth and to enhance their accelerated growth in later grades. Both hypotheses illuminate the sequential importance of developing and maintaining L 1 proficiency to the later emergence of L 2 • Supporting Cummins's (1979Cummins's ( , 1981Cummins's ( , 1984 theoretical framework is an emerging body of research including longitudinal evidence, which supports the positive out-101 comes of bilingual education program practices (Curiel, Rosenthal, & Richek, 1986;Medina & de la Garza, 1989;Medrano, 1986;Willig, 1985). Fernandez and Nielsen (1986), using a national data base, examined the effects of English and Spanish proficiency on high school Hispanics' academic achievement.…”
mentioning
confidence: 91%
“…A recent study by Medrano (1986) reported significant benefits in mathematics achievement for 179 Mexican-American students participating in a bilingual education program. Several scholars (Curiel, Rosenthal, & Richek, 1986) discovered that Hispanic secondary students exposed to an elementary bilingual education program experienced significantly less grade retention and lower dropout rates, and they were younger than Hispanic counterparts in an English-only traditional curriculum because of appropriate age-grade placements. In a study to determine the sustaining effects of an MBE program during Grades 1 through 5 across 7 subsequent years, researchers found that by the 12th grade MBE subjects were at or above national norms for English achievement in reading and mathematics.…”
mentioning
confidence: 98%